Survey of Multiobjective Evolutionary Algorithms for Data Mining: Part II - Mukhopadhyay, Anirban; Maulik, Ujjwal; Bandyopadhyay, Sanghamitra; Coello, Carlos A. Coello (IEEE transactions on evolutionary computation, 2014)
This paper is the second part of a two-part paper, which is a survey of multiobjective evolutionary algorithms for data mining problems. In Part I , multiobjective evolutionary algorithms used for feature selection and classification have been reviewed. In this part, different multiobjective evolutionary algorithms used for clustering, association rule mining, and other data mining tasks are surveyed. Moreover, a general discussion is provided along with scopes for future research in the domain of multiobjective evolutionary algorithms for data mining.